2018
DOI: 10.1016/j.injury.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Opioid exposure is associated with nonunion risk in a traumatically injured population: An inception cohort study

Abstract: Patients evaluated in this study were not a random sample of Americans; they may approximate a random sample of the Emergency Department population in the United States. Thus, trauma patients may represent a population enriched for nonunion risk factors. Opioids impair recovery from injury; if they also predispose to injury, the ongoing opioid epidemic could presage an increase in nonunion prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…Reid et al similarly found no difference in opioid utilization between prelaw and post-law cohorts after postoperative day 30 following lumbar spine surgery [29]. This is troubling as chronic opioid use has been linked to longer hospital stays, poorer quality of life, nonunion risk, and increased overall morbidity and mortality [16][17][18][19][20][21]35]. Preoperative opioid-tolerance appears to be the most consistent predictor of postoperative chronic use following ACDF, regardless of legislative efforts.…”
Section: Discussionmentioning
confidence: 99%
“…Reid et al similarly found no difference in opioid utilization between prelaw and post-law cohorts after postoperative day 30 following lumbar spine surgery [29]. This is troubling as chronic opioid use has been linked to longer hospital stays, poorer quality of life, nonunion risk, and increased overall morbidity and mortality [16][17][18][19][20][21]35]. Preoperative opioid-tolerance appears to be the most consistent predictor of postoperative chronic use following ACDF, regardless of legislative efforts.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,7,8 Prior research among surgical cohorts has demonstrated that sustained prescription opioid use is associated with increased perioperative morbidity, higher pain medication requirements, and decreased physical function. 2,3,[8][9][10] Among patients who sustain orthopedic trauma, regular opioid use has previously been shown to lower the likelihood of patient satisfaction 2,3 and increase the risk of nonunion. 9 One of the most substantive concerns around the use of prescription opioids in a trauma population is the potential for long-term sustained use after injury, especially in Table 1 e Demographics and clinical characteristics of orthopedic trauma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies dedicated to this issue are largely limited by varying degrees of the definition around opioid dependence and, perhaps most important, challenges with respect to surveillance of opioid use both before and after the traumatic event. [1][2][3][7][8][9][10] Furthermore, investigations conducted using data from single centers, or private health care insurance carriers may not have sufficient levels of clinical variation, or inherent risk of opioid dependence in the population under study, to allow generalization to the US population as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, there is a trend to reduce peri‐operative opioid prescribing. Both acute and chronic opioid prescriptions have been implicated in impaired bone healing and an increased risk of fracture non‐union . Epidural analgesia is associated with rare but potentially catastrophic risks, such as bleeding, infection and nerve damage.…”
Section: Discussionmentioning
confidence: 99%